Hubungan Motivasi dan Disiplin Belajar Terhadap Hasil Belajar Biologi Siswa Kelas XI SMA Negeri 1 Lirik Kabupaten Indragiri Hulu Tahun Ajaran 2021/2022 - Oni My Anjliani; Suryanti Suryanti (Peneliti.net, 2022)
This study aims to determine the relationship between learning motivation and learning discipline with the biology learning outcomes of class XI students of SMA N1Lyrics, Indragiri Hulu Regency for the Academic Year 2021/2022. The methodology of this research was carried out from April to June 2022. This type of research was correlational with data collection using questionnaires, interviews and documentation. The sample is 83 students. Data analysis using Person Product Moment correlation analysis. The results showed that the average of all motivation indicators was 86.31% very good category, the average of all learning discipline indicators was 86.06% very good category, the average student biology learning outcome was 77.00 moderate category. Furthermore, between motivation (X1), and learning discipline (X2) with learning outcomes (Y) there is a fairly high correlation with a correlation index (rxy) of 1.53%, the contribution of learning motivation and learning discipline to Biology learning outcomes of 3.11 %. This is also proven by the value of tcount (1.538) > ttable (0.677), which means H0 is rejected and Ha is accepted. 2021/2022.